Metabolic limitations of soil microorganisms during the decay of Salix psammophila sand barriers - Liang, Yumei; Duan, Xiaoting; Guo, Xin; Jia, Ruiting; Tian, Qi (Frontiers in Microbiology, 2025)
Salix psammophila sand barriers are the main measure used in desertification control engineering technology, which is widely used in China’s northwest desert region. To clarify the change characteristics and driving factors of soil enzyme stoichiometric ratios and microbial metabolic limitation during the decay of S. psammophila sand barriers, we determined soil basic physical and chemical properties and C:N:P stoichiometric ratios in the sand-buried portion of the S. psammophila sand barriers from 1 to 10 years. The results showed that (1) soil C:N showed an increasing trend, but soil N:P showed a decreasing trend over time. The activities of leucine aminopeptidase, β-1,4-n-acetylglucoside, and alkaline phosphatase first increased and then decreased with the increase of S. psammophila sand barrier years, and reached the maximum value at 6 years. (2) Redundancy analysis revealed that soil stoichiometric ratios were the main factors driving soil enzyme activities and their stoichiometry. (3) The soil enzyme C:N:P stoichiometric ratio was approximately 0.8:1:1. The enzyme vector lengths ranged from 0.66 to 1.09, and the vector angles ranged from 41.86° to 49.70°. Soil microorganisms were limited by nitrogen in the early stages (<5 years), while in the later stages (5–10 years) they were phosphorus-limited. Therefore, in the process of S. psammophila sand barriers assisting in the restoration of vegetation, it is considered to add an appropriate amount of nitrogen fertilizer to the soil in the first 5 years and add a small amount of phosphate fertilizer in the last 5 years to ensure ecosystem stability. Our findings are of great significance for artificial interventions for vegetation restoration and desert ecological conservation in desert areas.